Analysis of Photovoltaic Installations Performance and Deployment: Case Dubai Energy Sector - DHIMISH, AMEER (2024)
This thesis investigates the performance and degradation of photovoltaic (PV) systems in Dubai, a region characterized by its unique climatic conditions. With a growing emphasis on sustainable and clean energy, understanding the efficiency and longevity of PV installations in such environments is crucial. This study focuses on analyzing the Performance Ratio (PR) and degradation trends of two prevalent PV technologies: polycrystalline silicon (Poly-Si) and monocrystalline silicon (Mono-Si). Employing a comprehensive dataset provided by Al-Suwaidi Constructions, the research analyzed PV systems across various strategic locations in Dubai, including Jebel Ali, Al Qusais, Al Barsha, and Al Lisaili. These systems, integrated directly with the grid and varying in capacity from 1.5 MW to 2 MW, were scrutinized over a five-year period (January 2018 to December 2022). The methodology involved a detailed PR analysis using linear regression models to identify long-term trends and annual degradation rates. Key findings revealed that Poly-Si systems, despite being less efficient initially, exhibited lower annual degradation rates (-0.73% and -0.93%) compared to Mono-Si systems (-1.48% and -1.63%). This suggests a notable advantage in terms of stability and long-term performance for Poly-Si in harsh environments like Dubai. The study also contextualized these findings within the global landscape, comparing the performance of PV systems in various geographical settings. The research contributes significantly to the field of renewable energy, providing valuable insights for stakeholders in selecting appropriate PV technologies considering environmental conditions and long-term efficiency. It underscores the importance of tailored solutions in the deployment of sustainable energy technologies, particularly in regions facing extreme climatic challenges.